Biomechanics and Medicine in Swimming X (Portuguese Journal of Sport Sciences, 2006)
Topics Scientific topics Swimming Biomechanics Swimming Physiology and Biochemistry Swimming Bioenergetics Swimming Medicine and Traumatology Swimming Psychology